Assessing the relationship between english as a foreign language (EFL) teachers’ self-efficacy and their acceptance of online teaching in the Chinese context - Gao, Yanjun; Wong, Su Luan; Md. Khambari, Mas Nida; Noordin, Nooreen; Geng, Jingxin (MDPI, 2022)
This quantitative study investigated the relationship between EFL teachers’ self-efficacy and their acceptance of online teaching in the Chinese context. One online questionnaire, including a self-efficacy scale and behavioral intention scale, was administrated to 293 university-level EFL teachers in China. The descriptive results indicated that EFL teachers at Chinese universities possessed a positive intention to adopt online teaching and relatively high self-efficacy in embracing online teaching. Correlational analyses showed that all four aspects of the self-efficacy of EFL teachers—student engagement, instructional strategies, classroom management, and computer ability—had significant correlations with their acceptance of online teaching. Meanwhile, based on the results of multiple linear regression analyses, EFL teachers’ efficacy in student engagement and instructional strategies were predictors of their intention to teach online. Self-efficacy in classroom management and computer ability did not influence EFL teachers’ acceptance of online teaching. An in-depth understanding of the relationship between self-efficacy and EFL teachers’ behavior and intentions can allow teachers and educators to improve their self-confidence and engagement in online teaching at a pedagogical level and identify patterns in teacher efficiency with respect to language at a theoretical level.